Introduction to Social Media, Activism, and Organizations - Murthy, Dhiraj (Social media + society, 2018)
Social media have become increasingly pervasive. However, the literature on social movements and social media has not fully grasped just how much social media have fundamentally changed the landscape of organizational communication, ranging from stakeholders being able to directly mobilize resources to making grassroots transnational social movements more organizationally feasible. A major gap in the literature is this lack of understanding how social media have shaped social movement organizations (SMOs) and the organization of social movements. This Special Issue brings together a unique collection of articles that map and comment on the field of social media and social movements. The volume contributes to literature in this area by exploring how social media are not only shaping social movements, advocacy, and activism from the point of view of organizational communication but also changing the ways in which activists and SMOs interact with each other. The volume leverages a diverse array of interdisciplinary methods and covers a broad terrain ranging from analyses of knowledge transfer between grassroot activists via social media to large SMOs. The Issue is broadly divided into two parts. Part 1 is focused around trends and interventions in social media, activism, and organizations research. Part 2 revolves around a global collection of case studies. The two are hardly mutually exclusive and the boundaries are roughly drawn. This collection provides a critical starting point for better understanding social media and social movements, an area that is fundamentally important to a variety of disciplines but severely underresearched.